AUGMENTED REALITY LABELS FOR TEACHING FACTORY PRODUCT PRESENTATION IN A VOCATIONAL HIGH SCHOOL (MULTIMEDIA PROGRAM) - Herman Thuan To Saurik; Kelvin; Sigit Firdaus Prayogi; Taufikur Rahman (RADJA PUBLIKA, 2026)
This study implements the application of Augmented Reality (AR) on labels or packaging of Teaching Factory (TEFA) SMK Multimedia Program products. An R&D design with a Design Thinking framework (Empathize–Test) was used as a user-centered solution. The prototype was developed using Unity–Vuforia and tested on 55 respondents (50 students and 5 teachers) through questionnaires and observations. Descriptive results show strong support for the feasibility of AR as a presentation medium and practical teaching material. The packaging design results before AR were rated positively with a rating of Good–Very Good at 74.6%. The most appreciated AR element was 3D animation at 85.5%. From a promotional perspective, AR results were perceived as effective–very effective at 81.8%. In the field of vocational education, the description of industrial workflows was considered very comprehensive by the majority at 83.6%, with an adoption interest of 85.5%. The main challenges lie in the application of usability and technical complexity (rated as difficult and very difficult by 60.0%), so improvements to the UI/UX, optimization of 3D asset quality, and the addition of CTA features (buy/location/QR links) are recommended. These findings indicate that the application of AR label technology increases appeal, enriches product understanding, and is relevant as a TEFA project module, while also opening up room for improvement in usability and content pipeline to ensure the sustainability of implementation in vocational learning at SMK Multimedia Program.